2002
DOI: 10.1136/gut.51.5.712
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of oestrogen receptor, progesterone receptor, trefoil factor 1, and epidermal growth factor and its receptor in pancreatic cystic neoplasms and pancreatic ductal adenocarcinoma

Abstract: Background and aims: The pancreatic cystic neoplasms, including solid pseudopapillary tumour (SPT), mucinous cystic neoplasm (MCN), and intraductal papillary mucin producing tumour (IPMT), have their characteristic clinicopathological features. A systematic investigation of oestrogen receptor (OR), progesterone receptor (PR), trefoil factor 1(TFF1), and epidermal growth factor and its receptor (EGF and EGFR) expressed in pancreatic cystic neoplasms and pancreatic ductal adenocarcinoma was determined to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 21 publications
2
33
0
1
Order By: Relevance
“…EGFR is overexpressed in a wide variety of epithelial neoplasms, including pancreatic cancer. 16,17 With regard to cystic neoplasms of the pancreas, Yeh et al 28 and Zhao et al 29 independently found that EGFR is infrequently expressed in the mucinous cystic neoplasms. However, there have been no published reports on EGFR expression in the serous cystic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is overexpressed in a wide variety of epithelial neoplasms, including pancreatic cancer. 16,17 With regard to cystic neoplasms of the pancreas, Yeh et al 28 and Zhao et al 29 independently found that EGFR is infrequently expressed in the mucinous cystic neoplasms. However, there have been no published reports on EGFR expression in the serous cystic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies indicate that TFF1 expression is absent or occurs at low levels in nonmalignant pancreatic and prostate tissues. Elevated expression levels of TFF1 are frequently observed in pancreatic and prostate malignancies (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), suggesting that TFF1 may be involved in the tumorigenesis of these cancers. These data are not, however, sufficiently convincing because of the lack of strict statistical analysis in some studies and the reduced statistical power in others with small sample sizes.…”
Section: Tff1 Expressionmentioning
confidence: 99%
“…To gain insight into this question, we took a candidate approach by examining the possible involvement of known signaling pathway(s) initiated by plasma membrane-bound receptors for growth factors for mediation of TFF1 activity in the context of overcoming OIS. In this regard, previous reports indicated that TFF1 and EGFR are co-overexpressed in certain malignant tumors and that TFF1 might exert its activity through EGFR, although no definitive signaling pathways have been elucidated (31). To test if EGFR activity contributes to the ability of TFF1 to suppress OIS, we repeated the experiment using PrEC with Ras-induced OIS and recombinant TFF1 in the presence or absence of an EGFR inhibitor.…”
Section: Egfr Activity Is Required For Tff1 To Overcome Ois and Loss mentioning
confidence: 99%
“…In animal models, sunitinib exhibits potent antitumor activity in glioblastoma, breast and lung tumors (28,29). In human PC, VEGFRs types 1-3 and PDGFRs · and ß are expressed and have been correlated with poor prognosis (30)(31)(32)(33). Also, recently, it was demonstrated in vitro and in vivo that sunitinib sensitized pancreatic cancer cells to the cytotoxic effects of radiation (34).…”
Section: Introductionmentioning
confidence: 99%